“Loneliness is a sad disease”: oldest old adults’ empirical definition of loneliness and social isolation from a mixed-method study in Northern Italy - Sara Santini; Mauro Colombo; Antonio Guaita; Paolo Fabbietti; Georgia Casanova (BMC Geriatrics)
Abstract Background Loneliness and social isolation can occur at any stage of life, but some predictors may be more common among older adults. Due to growing population ageing, loneliness and social isolation are relevant social issues. Many studies apply the main definitions of loneliness and social isolation offered by the literature without considering how individual representations, socio-cultural context and the culture of care may influence their perception. This study wishes to fill in these literature gaps by analysing empirical definitions of loneliness and social isolation arising from a mixed-gender randomized sample of Italian oldest old people. Methods Between January and March 2019, 132 older people, most aged 80+, living in a northern Italian town, were asked to answer a questionnaire and a semi-structured interview. According to a mixed-method analysis the definitions of loneliness and social isolation were analysed by respondents’ gender, living arrangement (e.g., living alone or with partners or other people), and years of education to find possible associations to the meanings attributed to the two concepts. Results The sample was gender-balanced and mid-low educated; more than one fourth of respondents lived alone. The results underline how the empirical definitions of loneliness and social isolation are closer to each other than the academic ones. The two concepts are often perceived by participants as distinct, but they are strongly interconnected so that they can be used interchangeably by older Italian people. The two main themes identified by the analysis are loneliness as “death” and social isolation as “guilt”. In the respondents’ opinion, the main loneliness driver is the loss of loved, close persons, while social isolation is driven by disability. Age, educational level, and living arrangements did not influence the meanings attributed to social isolation. On the contrary, living arrangement (P = 0.002) and educational level (p = 0.023) seem to influence the empirical definitions of loneliness. Conclusion The knowledge of the meanings that oldest old give to the two concepts may inspire advanced intervention aimed at buffering the psychological and social consequences of loneliness and social isolation in the older population.